Molecular Systematics of the Cape Parrot (Poicephalus robustus): Implications for Taxonomy and Conservation - Coetzer, Willem G.; Downs, Colleen T.; Perrin, Mike R.; Willows-Munro, Sandi (PLOS ONE, 2015)
The taxonomic position of the Cape Parrot (Poicephalus robustus robustus) has been the focus of much debate. A number of authors suggest that the Cape Parrot should be viewed as a distinct species separate from the other two P. robustus subspecies (P. r. fuscicollis and P. r. suahelicus). These recommendations were based on morphological, ecological, and behavioural assessments. In this study we investigated the validity of these recommendations using multilocus DNA analyses. We genotyped 138 specimens from five Poicephalus species (P. cryptoxanthus, P. gulielmi, P. meyeri, P. robustus, and P. rueppellii) using 11 microsatellite loci. Additionally, two mitochondrial (cytochrome oxidase I gene and 16S ribosomal RNA) and one nuclear intron (intron 7 of the β-fibrinogen gene) markers were amplified and sequenced. Bayesian clustering analysis and pairwise FST analysis of microsatellite data identified P. r. robustus as genetically distinct from the other P. robustus subspecies. Phylogenetic and molecular clock analyses on sequence data also supported the microsatellite analyses, placing P. r. robustus in a distinct clade separate from the other P. robustus subspecies. Molecular clock analysis places the most recent common ancestor between P. r. robustus and P. r. fuscicollis / P. r. suahelicus at 2.13 to 2.67 million years ago. Our results all support previous recommendations to elevate the Cape Parrot to species level. This will facilitate better planning and implementation of international and local conservation management strategies for the Cape Parrot.